THE EFFECT OF USING “EASY GERMAN” VIDEOS TOWARD STUDENT’S LEARNING OUTCOMES IN LEARNING GERMAN STRUCTURE - Grietje Hanna Kunu; Carolina Lestuny (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2023)
This research was conducted to examine the effect of using videos on the YouTube channel “Easy German” toward student’s learning outcomes, especially the language structure. This research was carried out in September 2022. This research is an experimental research with one group pre-test and post-test design. The samples in this study were 15 students of the German Education Study Program who were in the 3rd Semester of the academic year 2022/2023 and taking Structural 3 Course. This study consists of 2 variables, the first variable is the independent variable, namely the video channel ““Easy German”.” The second variable is the dependent variable, namely the learning outcomes of German structure. The data were analyzed using the independent t-test formula which was used to measure the mean difference in the students’ language structure with an average score after using the videos on this channel, namely 75.67. This is inversely proportional to the average score of students before using the videos on the “Easy German” channel, which was 58.67. Therefore, it is suggested to implement the videos on the “Easy German” channel in German classes to improve student learning outcomes especially German structure.